Memperkuat Pemahaman Tri Hita Karana Melalui Upacara Ngaturang Cicipan: Perspektif Etnopedagogik - I Made Ardika Yasa; I Wayan Suastra; Ida Bagus Putu Arnyana (Cetta: Jurnal Ilmu Pendidikan, 2023)
This research aims to gain a deeper understanding of the Tri Hita Karana concept through the utilization of an ethnopedagogical approach within the Ngaturang Cicipan Ceremony, a traditional cultural ritual conducted by the community of Dusun Rincung in the village of Banyu Urip, Gerung District, West Lombok Regency, West Nusa Tenggara Province. The Tri Hita Karana concept, which encompasses the balance of human relationships with the divine, fellow humans, and nature, holds profound significance in the local culture and has the potential to enrich environmental and spiritual perspectives. This study employs an ethnopedagogical approach to integrate the elements of Tri Hita Karana into the Ngaturang Cicipan Ceremony with the objective of enhancing community understanding and awareness of Tri Hita Karana values.  The research methodology involves qualitative data collection through participatory observation, interviews, and content analysis. The findings reveal that the implementation of ethnopedagogy in the Ngaturang Cicipan Ceremony successfully reinforces the community's comprehension and appreciation of the Tri Hita Karana concept. Active participation in the ceremony enriched with Tri Hita Karana elements has helped elevate environmental consciousness, social values, and spiritual aspects in the daily lives of the community.  This research contributes to our understanding of how an ethnopedagogical approach can be used to deepen cultural values and philosophy in the context of traditional cultural practices. These findings also underscore the significance of local culture in comprehending and addressing environmental challenges and enhancing the quality of life for the community. The implications of this research can serve as a foundation for developing more contextual and sustainable educational programs that promote harmony among humans, nature, and spirituality.